Lembaga Lokal dan Masyarakat Dalam Pemenuhan Kebutuhan Rumah Bagi Masyarakat Berpenghasilan Rendah - Arimurty, Anggi; Manaf, Asnawi (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2013)
Pekalongan City is one of the city in Indonesia who got the trust from the Ministry of People Housing to fulfill the needs of the livable housing for low incomes people through Rumah Inti Tumbuh (RIT). To enable low-income people access the formal housing, Pekalongan Government partnered with local institutions and low-income people itself. The purpose of this research is to examine the partnership system between local governments, local institution, and the community in fulfilling the needs of the livable housing for low incomes people which occurred in Pekalongan City. This research used the qualitative approach with in-depth interviews, observation method, field, and documents study. Analytical techniques used was qualitative descriptive). The research results obtained that the houses fulfillment mechanism system in the Pekalongan City cannot be released from the aspect of the provision of land and public facilities, low income communities selection of administration and finance, development stage by developing cooperative role as a developer of housing, and financing by utilizing Credit development/self help home improvement micro subsidized from the Ministry of People Housing. As for the pattern of the partnership the partnership model form composed mutualisme when juxtaposed with the partnership of the theory of Sulistiyani (2004: 131).